Administrative Juristic Acts Generated by Automated Systems: Legal Status and Completeness of Will in Thai Administrative Law - Wantha, Kampon (Journal of Dhamma for Life, 2026)
This research aims to examine the legal status of administrative acts generated by automated systems under Thai administrative law, with particular reference to the Administrative Procedure Act B.E. 2539 (1996). The objectives of the study are threefold: (1) to analyze whether administrative decisions produced through algorithmic or automated processes satisfy the legal requirements for the formation of administrative acts, especially the requirement of intention; (2) to examine the concept of “completeness of intention” in automated decision-making in order to assess whether such systems can be deemed to possess legally relevant intent; and (3) to conduct a comparative study of foreign legal approaches, including those of Germany, France, and the European Union, regarding the recognition and regulation of automated administrative decision-making, and to propose legal and policy recommendations for the reform of Thai law in the digital era. This study employs doctrinal legal research methodology. The population of the research consists of statutory provisions, administrative court judgments, legal theories, and relevant academic literature. The research instruments include documentary analysis and qualitative legal interpretation, using Will Theory and the principle of completeness of intention as the main analytical framework. Key provisions of the Administrative Procedure Act B.E. 2539, particularly Sections 5, 30, 41, 42, and 44, are examined in conjunction with judicial interpretations and comparative legal materials. The findings indicate that administrative orders generated solely by automated systems cannot currently be regarded as valid administrative acts under Thai law, as they lack the essential element of intention on the part of the authorized administrative official. Such practices may also conflict with the principles of legality and transparency. Accordingly, the study concludes that the use of automated systems in administrative decision-making must be accompanied by clear mechanisms for attributing and supervising administrative intent, in order to ensure compliance with the rule of law and the protection of individual rights in the digital age.